“A Grey Wee Town”: An Environmental History of Early Silver Mining at Cobalt, Ontario - Baldwin, Douglas; Duke, David (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2005)
Cobalt was Ontario's first mining-boom town and at its height was the world's fourth-largest producer of silver. The initial discovery of silver in 1903 led to a rush that saw the town grow to several thousand inhabitants within a decade. In this period, land values rose to astronomical heights, thousands of claims were laid, and the town was hemmed in by mining operations. Initially the mines were relatively small-scale and used simple technology, but soon major mining interests impinged on the town geographically and severely affected it politically and economically. The mining-boom story of Cobalt takes the form of a conflict between the town council on the one hand and powerful mining concerns on the other. The former struggled to provide a reasonable standard of living for Cobalt's inhabitants, while the latter attempted to extract as much silver as quickly as possible from the surrounding land, from beneath neighbouring lakes, and even from within the townsite itself. In this struggle both the urban and natural environments suffered: financial constraints and near-unrestricted mining production resulted in a thoroughly inadequate urban infrastructure, especially in the provision of water for the town's inhabitants, while unhindered mining systematically deforested and denuded the land around the town and even drained the town's original main source of water, Cobalt Lake. Today, almost a century after the silver industry began to decline, the Cobalt region still displays the environmental impact of the mining activities of those early, rush years.